Ramón Indalecio Cardozo (1876-1943). Pioneer of the Paraguayan Active School - Soto Vera, Anahí Concepción; Velázquez Seiferheld, David (Revista Historia de la Educación Latinoamericana, 2019)
Paraguayan teacher Ramón Indalecio Cardozo (1876-1943) is considered the father of the Paraguayan Escuela Nueva Model. He dedicated his life to the integral improvement of the education quality of the country. This article aims to review his life and work, and makes emphasis on the contributions he made to both pedagogy and the working conditions of Paraguayan teachers. Some of his works and textbooks were consulted, especially those related to pedagogical principles and guidelines. Documentary research was used as a method for this review. The results obtained from books, articles, pamphlets and manuals published by Cardozo were analyzed, systematized and integrated, as well as complementary data on his life and about the impact of his contributions. Recently, interest in Cardozo’s proposals has increased; however, it is still necessary to deepen the rescue and understanding of his work beyond the partisan, religious and nationalist biases that have overshadowed his memory to the present day. His educational project was crystallized in Reform 22/24, which did not thrive off, but his legacy is still valid, mainly for teachers who encourage curiosity and democracy in the classroom, even amid personalist pressures and interests alien to education.